Vaginal atrophy – diagnostics and treatment - Drews, Krzysztof; Pieńkowski, Wojciech; Perlik, Michał (Menopause Review/Przegląd Menopauzalny, 2005)
Menopause is associated with a marked reduction in endogenous estrogen production. Lower levels of circulating blood estrogen have various deleterious effects including those on the lower urogenital tract. This aim of this paper is to review the recent evidence regarding the etiology and the management of post-menopausal urogenital atrophy, especially different forms of local hormonal therapy.